Reduced Effect of Aspirin on Thrombus Formation at High Shear and Disturbed Laminar Blood Flow - Marius Barstad, R; Ørvim, Una; Hamers, Maria J A.G; Tjønnfjord, Geir E; Brosstad, Frank R; Sakariassen, Kjell S (Thrombosis and Haemostasis, 1996)
Aspirin is the most commonly used antithrombotic drug in primary and secondary prophylaxis against cardio- and cerebrovascular disease. In previous studies from our laboratory it was demonstrated that the effect of aspirin on collagen-induced thrombus formation in a parallelplate perfusion device with laminar blood flow is shear rate dependent. Although aspirin did not affect collagen-induced thrombus formation at 650 s-1 (medium sized arteries), a significant inhibition of thrombus formation by approximately 38% at 2,600 s-1 (moderately stenoses in medium sized arteries) was observed. At present we have extended these studies to thrombus formation at the apex of eccentric stenoses in a parallel-plate perfusion chamber device. The stenoses reduced the cross-sectional area of the blood flow channel of the perfusion chambers by 60 or 80%, introducing disturbed laminar flow and apex wall shear rates of 2,600 and 10,500 s-1, respectively. The corresponding wall shear stresses were 80 and 315 dynes/cm2, respectively.Aspirin reduced the platelet thrombus volume at the 60% stenosis by 45% (p <0.03), and the fibrin deposition by 70% (p <0.004). However, none of these parameters were affected by aspirin at the 80% stenosis. These observations may at least partly explain why aspirin has a limited clinical effect in preventing arterial thrombus formation in atherosclerotic vessels at high shear and disturbed blood flow. In contrast, thrombus formation in blood from one patient with Glanzmann’s thrombasthenia and two patients with von Willebrand disease subtype 2M was almost abolished at this blood flow condition. Thus, blocking the function of either von Willebrand factor or glycoprotein IIb/IIIa may represent better antithrombotic approaches for such critical events than blocking the prostaglandin metabolism by aspirin. The lack of effect of aspirin on thrombus formation at the 80% stenosis may reflect shear-induced platelet activation at the stenosis inlet region, since shear-induced platelet aggregation in rotational viscometers is not affected by aspirin at shear stresses exceeding 100 dynes/cm2.